Contingent Convertible Bonds (Cocos) Issued by European Banks - Kjell Bjørn Nordal; Nicolas Stefano (Norges Bank, 2014)
During the recent global financial crisis, numerous banking institutions faced acute capital strain. In order to support banking sectors, many governments stepped in and propped up financial institutions, often at the expense of the taxpayer. As a result, much regulatory work has focused on implementing measures to improve the resiliency of the banking sector. Enhancing the effectiveness of capital buffers as well as the ability to efficiently resolve banks both on a going-concern and gone-concern basis have been a few of the primary goals of recent regulatory efforts. Contingent convertible (Coco) bonds have increased in popularity during recent years, as banks have sought to expand the robustness of their respective capital buffers and meet new, higher regulatory requirements. Coco bonds are hybrid securities, which can serve to function as equity under certain circumstances and, therefore, may qualify as regulatory capital under Basel III standards. Key characteristics of Coco bonds are that they maintain the following contractual aspects: 1) a pre-defined trigger mechanism, and 2) loss-absorption capacity. This memo will review the main features of Cocos and will also analyse observations in practice so as to provide an overview of European Coco market issuance, as well as pricing considerations.
hdl:11250/2506899
Keywords: 330